Concurrent hypoxia and apoptosis imparts immune programming potential in mesenchymal stem cells: Lesson from acute graft-versus-host-disease model - Mohini Mendiratta; Meenakshi Mendiratta; Shuvadeep Ganguly; Sandeep Rai; Ritu Gupta; Lalit Kumar; Sameer Bakhshi; Vatsla Dadhwal; Deepam Pushpam; Prabhat Singh Malik; Raja Pramanik; Mukul Aggarwal; et al. (Stem Cell Research & Therapy)
Abstract Background Mesenchymal stem cells (MSCs) have emerged as promising candidates for immune modulation in various diseases that are associated with dysregulated immune responses like Graft-versus-Host-Disease (GVHD). MSCs are pleiotropic and the fate of MSCs following administration is a major determinant of their therapeutic efficacy. Methods Human MSCs were derived from bone marrow (BM) and Wharton’s Jelly (WJ) and preconditioned through exposure to hypoxia and induction of apoptosis, either sequentially or simultaneously. The immune programming potential of preconditioned MSCs was evaluated by assessing their effects on T cell proliferation, induction of Tregs, programming of effector T-cell towards Th2 phenotype, macrophage polarization in the direct co-culture of MSCs and aGVHD patients-derived PBMNCs. Additionally, efferocytosis of MSCs and relative change in the expression of immunomodulatory soluble factors were examined. Results Our study demonstrated that hypoxia preconditioned apoptotic MSCs (BM-MSCs, WJ-MSCs) bear more immune programming ability in a cellular model of acute Graft-versus-Host-Disease (aGVHD). Our findings revealed that WJ-MSCsHYP+APO were superior to BM-MSCsHYP+APO for immune regulation. These induced the differentiation of CD4+T-cell into Tregs, enhanced Th2 effector responses, and simultaneously mitigated Th1- and Th17 responses. Additionally, this approach led to the polarization of M1 macrophages toward an M2 phenotype. Conclusion Our study highlights the potential of WJ-MSCs conditioned with hypoxia and apoptosis concurrently, as a promising therapeutic strategy for aGVHD. It underscores the importance of considering MSC apoptosis in optimizing MSCs-based cellular therapy protocols for enhanced therapeutic efficacy in aGvHD. Graphical Abstract